Case Report: A Case of COVID Vaccine-Induced Thrombotic Thrombocytopenia Manifested as Pulmonary Embolism and Hemorrhagia. A First Reported Case From Slovakia - Ihnatko, Martin; Truchla, Ivana; Ihnatková, L'udmila; Prohászka, Zoltán; Lazúrová, Ivica (Frontiers in Medicine, 2022)
COVID-19 vaccine-induced thrombotic thrombocytopenia (VITT) is a rare complication of adenoviral vector (ChAdOx1 nCoV-19) vaccine administration. It is presented as thrombocytopenia and thrombotic manifestations in various sites, especially in cerebral veins. Pulmonary emboli have been reported rarely. We present a case of a young male patient who developed severe thrombocytopenia and pulmonary embolism 12 days after the first dose of the vaccine. Severe thrombocytopenia, skin hematomas, and segmental pulmonary emboli were detected. Anti-platelet factor 4 (aPF-4) antibody was highly positive supporting the diagnosis of VITT. Prompt treatment with fondaparinux, intravenous immunoglobulin, and prednisone led to a marked improvement of clinical condition and thrombocytes count. We report the first known case of VITT in Slovakia.